Alanine aminotransferase and mortality in patients with type 2 diabetes (ZODIAC‐38). (3rd July 2015) - Deetman, Petronella E.; Alkhalaf, Alaa; Landman, Gijs W.D.; Groenier, Klaas H.; Kootstra‐Ros, Jenny E.; Navis, Gerjan; Bilo, Henk J.G.; Kleefstra, Nanne; Bakker, Stephan J.L.
Abstract Introduction Combined data suggest a bimodal association of alanine aminotransferase (ALT) with mortality in the general population. Little is known about the association of ALT with mortality in patients with type 2 diabetes. We therefore investigated the association of ALT with all‐cause, cardiovascular and noncardiovascular mortality in patients with type 2 diabetes. Design A prospective study was performed in patients with type 2 diabetes, treated in primary care, participating in the Zwolle Outpatient Diabetes project Integrating Available Care (ZODIAC) study. Cox regression analyses were performed to determine the associations of log2‐transformed baseline ALT with all‐cause, cardiovascular and noncardiovascular mortality. Results In 1187 patients with type 2 diabetes (67 ± 12 years, 45% female), ALT levels were 11 (8–16) U/L. During median follow‐up for 11·1 (6·1–14·0) years, 553 (47%) patients died, with 238 (20%) attributable to cardiovascular causes. Overall, ALT was inversely associated with all‐cause mortality (hazard ratio [HR] 0·81; 95% confidence interval [CI] 0·72–0·92), independently of potential confounders. This was less attributable to cardiovascular mortality (HR 0·87; 95% CI 0·72–1·05), than to noncardiovascular mortality (HR 0·77; 95% CI 0·65–0·90). Despite the overall inverse association of ALT with mortality, it appeared that a bimodal association with all‐cause mortality was present with increasing risk for levels of ALT above normal (P = 0·003). Discussion In patients with type 2 diabetes, low levels of ALT are associated with an increased risk of all‐cause mortality, in particular noncardiovascular mortality, compared to normal levels of ALT, while risk again starts to increase when levels are above normal.